2019
DOI: 10.1039/c8tc05430d
|View full text |Cite
|
Sign up to set email alerts
|

Structure, luminescence and energy transfer in Ce3+ and Mn2+ codoped γ-AlON phosphors

Abstract: Upon UV or blue light excitation, the codoped γ-AlON phosphor has higher luminescence intensity, quantum efficiency and thermal stability than the Mn2+-doped γ-AlON due to energy transfer and low total concentration of Ce3+ and Mn2+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The experiment verified the relevant information, and a large number of studies reported that Ce 3+ transfers energy to Mn 2+ and examples of Mn 2+ ion transferring energy to Ce 3+ have not been found. 34–39 Furthermore, the experiment measured the lifetime change of Mn2 luminescence center with Ce 3+ doping, as shown in Fig. 9(b) .…”
Section: Resultsmentioning
confidence: 99%
“…The experiment verified the relevant information, and a large number of studies reported that Ce 3+ transfers energy to Mn 2+ and examples of Mn 2+ ion transferring energy to Ce 3+ have not been found. 34–39 Furthermore, the experiment measured the lifetime change of Mn2 luminescence center with Ce 3+ doping, as shown in Fig. 9(b) .…”
Section: Resultsmentioning
confidence: 99%
“…With reference to each other or sometimes to an original paper by Dexter and Schulman, it is stated that these ratios are expected to increase with the Mn 2+ concentration C proportional to C 6/3 (dipole–dipole), C 8/3 (dipole–quadrupole), or C 10/3 (quadrupole–quadrupole). Often the best fit was obtained for C 8/3 , and a dipole–quadrupole ET mechanism was thus concluded. Sometimes a better fit was found for C 6/3 or C 10/3 and was used to derive that dipole–dipole or quadrupole–quadrupole interaction was the operative transfer mechanism. , Finally, it is important to realize that these C S /3 vs I S0 / I S , η S0 /η S , or τ S0 /τ S fitting methods to derive ET mechanisms are also widely used for other donor–acceptor pairs, for example, Tb 3+ → Eu 3+ . The C S /3 model is widespread but, as will be shown below, incorrect for donor–acceptor energy transfer as it has been derived for concentration quenching by energy migration among donors.…”
Section: Resultsmentioning
confidence: 99%
“…Absorption transitions from the 6 A 1 ground state to the 4 T 1 and 4 T 2 excited states of Mn 2+ are spin- and parity-forbidden. To tackle the weak d–d absorption, codoping with sensitizers having allowed transitions (f–d in Eu 2+ , Ce 3+ ; s–p in Sn 2+ , Sb 3+ , Pb 2+ , Bi 3+ ) with effective absorption of blue excitation light can be the solution if efficient nonradiative energy transfer to Mn 2+ ions can be realized. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar situation can also be found in Ce 3+ -Mn 2+ codoped γ-AlON phosphor. 35 The η T is possible to be further increased by increasing Mn 2+ doping concentration, but the increasing concentration quenching of Mn 2+ may result in low emission efficiency as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%